2019
DOI: 10.1016/j.ijppaw.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and negative interactions in low-diversity and unsaturated monogenean (Platyhelminthes) communities in Astyanax aeneus (Teleostei) populations in a neotropical river of Mexico

Abstract: We studied monogenean communities of 11 populations of Astyanax aeneus (Günther) separated by small geographical distances along 60 km of the Lacantún river in Chiapas, Mexico, in February and August 2012. We found 12 monogenean taxa. Amongst these, five species specialist for Astyanax were widely distributed regionally, constituting 90% of the total collected monogeneans, with one of these species dominating most component communities. The high similarities in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
4
13
0
Order By: Relevance
“…We assessed the level of aggregation of helminth populations to test their influence on determining the local parasite richness within a host population. Further, we assessed whether intraspecific aggregation exceeded interspecific aggregation (e.g., Salgado-Maldonado et al, 2019). Our goal was to explore the factors that might contribute to the richness and coexistence of helminth parasites of P. bimaculatus across 11 localities in the La Antigua River, a neotropical system in Veracruz, Mexico.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the level of aggregation of helminth populations to test their influence on determining the local parasite richness within a host population. Further, we assessed whether intraspecific aggregation exceeded interspecific aggregation (e.g., Salgado-Maldonado et al, 2019). Our goal was to explore the factors that might contribute to the richness and coexistence of helminth parasites of P. bimaculatus across 11 localities in the La Antigua River, a neotropical system in Veracruz, Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…Additional empirical support by Vidal‐Martínez and Kennedy (2000) showed that even relatively small numbers of acanthocephalans can produce a displacement of phylogenetically unrelated intestinal helminths (trematodes and nematodes) in a tropical cichlid fish, Cichlasoma synspilum . We recently described the potential interactions in low‐diversity monogenean parasitic communities in a tropical freshwater fish, Astyanax aeneus , and showed that interspecific interactions can be an important factor for structuring low‐diversity ectoparasitic helminth communities (Salgado‐Maldonado, Mendoza‐Franco, Caspeta‐Mandujano, & Ramírez‐Martínez, 2019). Thus, the extent to which interspecific interactions are important structuring factors for low‐diversity fish ecto‐ and endoparasite communities remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, C. grammodes feeds mainly on aquatic insects (e.g., Trichoptera, Odonata, Megaloptera) and small fish that might produce little variation on their community descriptors (species richness, diversity) and infection parameters (mean abundance) between host species (Violante-González et al, 2008a,b;Gómez-González et al, 2015 Kennedy, 1996;Salgado-Maldonado et al, 2005). Generally, helminth communities in freshwater fish are isolationist in structure and stochastic in composition, thus reflecting their low species richness and diversity (see Vidal-Martínez & Kennedy, 2000;Kennedy, 2006;Salgado-Maldonado et al, 2019). This pattern is probably due to several factors, such as geography and geology (contemporary and past) of regions and drainages, different environmental conditions, historical ecology of both hosts and parasites, feeding behavior and specializations of the host, which contribute to the structuration of the communities of parasites (Choudhury & Dick, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Overall component communities in the three cichlids were poor in species and number of metazoans, when comparing with other tropical cichlids: Mayaheros urophthalmus (Günther, 1862) group (= Cichlasoma urophthalmum ) (38 species), Parachromis managuensis (34 species), Thorichthys helleri (32 species), Vieja fenestrata (= Cichlasoma fenestratum ) (37 species) and Petenia splendida (27 species) ( Salgado-Maldonado & Kennedy, 1996 ; Salgado-Maldonado et al, 2005 ). Generally, helminth communities in freshwater fish are isolationist in structure and stochastic in composition, thus reflecting their low species richness and diversity (see Vidal-Martínez & Kennedy, 2000 ; Kennedy, 2006 ; Salgado-Maldonado et al, 2019 ). This pattern is probably due to several factors, such as geography and geology (contemporary and past) of regions and drainages, different environmental conditions, historical ecology of both hosts and parasites, feeding behavior and specializations of the host, which contribute to the structuration of the communities of parasites ( Choudhury & Dick, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“… Data source location MEXICO (south of the country), state of Chiapas. Eleven sample locations situated on the opening of streams tributaries to the main Rio Lacantún in the Biosphere Reserve Montes Azules (RBMA), Chiapas, México: [1] Río Tzendales (16°17′ 10.8″ N; 90°53′12.6″ W), [2] Río Manzanares (16°10′14.6″ N; 90°50′36.2″ W), [3] Arroyo Miranda (16°08′08.1″ N; 90°55′14.9″ W), [4] Río Danta (16°09′08.1″ N; 90°54′06.3″ W), (5) Arroyo Lagarto (16°08′14.0″ N; 90°54′24.4″ W), (6) Embarcadero Estación Chajul (16°06′38.4″ N; 90°56′ 23.6″ W), (7) Arroyo José (16°06′50″ N; 90°56′03.3″ W), (8) Río Chajul (16°05′58.2″ N; 90°57′30.1″ W), (9) Río San Pablo (16°06′ 10.0″ N; 91°00′52.2″ W), (10) Río Puerto Rico (16°05′04.4″ N; 91°01′11.2″ W), (11) Río Ixcan (16°07′17.5″ N; 91°05′11.3″ W). Data accessibility Data provided within this article.…”
mentioning
confidence: 99%